Peran Perawat sebagai Edukator dalam Mencegah Komplikasi Diabetes Melitus - Sri Indaryati; Lilik Pranata (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
The prevalence of diabetes mellitus, its complications and client visits to the health center are increasing every year. This will have a negative impact on the productivity of the client and the cost of treatment is very large due to diabetes complications. Some clients say it is difficult to control blood sugar. The International Diabetes Management Practices Study (IDMPS) reports that most diabetes clients have not received education. Only 36.1% of clients have received education. Endocrinologists admit that health workers have not optimally handled diabetes cases. Nurses in the field of non-communicable diseases at the Palembang City Health Center also admitted that they had not been optimal in providing education to clients with diabetes. The aim of this study was to determine the role of nurses as educators in preventing complications of diabetes mellitus using a descriptive analytic survey. All clients with diabetes in the Talang Betutu Health Center Work Area for 4 months in 2019 are the target population. The target population is 202 and the sample is taken from the total sampling of the target population visiting in June totaling 51 respondents. Data were taken using a questionnaire and the results were analyzed using univariate statistics. Research results: 55% of respondents stated that the role of nurses was good and 45% said that it was still not good. 57% of respondents stated that educational strategies were still lacking, but 83% of nurses' attitudes were good. 34% of respondents stated that nurses were still unclear in explaining blood sugar control, 50% stated that explanations for preventing acute complications were still lacking and explanations for preventing chronic complications such as heart disease, hypertension and kidney 70% stated that they were still unclear. Conclusion: The role of nurses as diabetes educators still needs to be improved so that complications can be minimized.